PENGELOLAAN PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI BERBASIS SNI ISO 9001:2008 - Subardi Subardi (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
This paper attempts to address the problem of how to manage the State Islamic Religious College (PTKIN) based on ISO 9001: 2008. Problems become important because in the era of the Industrial Revolution 4.0, quality human resources (HR) cannot be bargained again. The only way to improve the quality of human resources is through education, especially higher education institutions, including the State Islamic Religious College (PTKIN). So that the quality of PTKIN is not less competitive with other universities in Indonesia, the management of PTKIN must be based on ISO 9001: 2008 as one of the principled quality management of TQM in detailed and systematic application. The ISO 9001: 2008 system is a means or tool of PTKIN to achieve the expected quality objectives and is able to answer the challenges of the current Industrial Revolution 4.0 era. In addition, there is a periodic internal quality audit requirement. At present ISO 9001: 2008 is the main choice for higher education institutions, PTKIN to implement a quality management system consistently and systematically to achieve effectiveness and efficiency. The application of ISO 9001: 2008 at PTKIN is very important as a step to realize and provide good governance, achieve excellent education practices, improve customer satisfaction and provide a better response to industry needs. PTKIN's main motive for implementing ISO 9001: 2008 is as a promotional step to provide an overview that PTKIN has high quality, high visibility and credibility, response to external factors and to develop an overall quality management system, so as to provide services and output the best that can guarantee the satisfaction of all customers and stakeholders.